MEANS THAT MAKE UP THE SEEDLINGS IN POETRY - Rajabov, To’xtamurod (FILOLOGIYA UFQLARI JURNALI, 2024)
Movement can also occur in poetry by exchanging the place of the word series among themselves. We can understand the identity of the image in which the idea is drawn, depending on the application of the suffixes of the person-number in this process. At the same time, in the process of analyzing artistic seedlings in the period of independence, the concept of harvesting seedlings by means of pictorial expressions is widely formed. For example, the singer of happiness and joy – H. Frail, like a mirror – magazine of life. In general, the loops sometimes serve as a way for the speaker’s opinion to reach others, for example, exactly to the person to whom the speech is being paid. Well, the application of transports in the process of poetry serves to express the main idea that must be understood from the poem. This will perform the task of saving the word and getting rid of the repetition of speech.